2016
DOI: 10.1371/journal.pone.0167650
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aryl Hydrocarbon Receptor Agonist Suppresses Migration and Invasion of Breast Cancer Cells

Abstract: BackgroundDespite the remarkable progress to fight against breast cancer, metastasis remains the dominant cause of treatment failure and recurrence. Therefore, control of invasiveness potential of breast cancer cells is crucial. Accumulating evidences suggest Aryl hydrocarbon receptor (Ahr), a helix-loop-helix transcription factor, as a promising target to control migration and invasion in breast cancer cells. Thus, an Ahr-based exploration was performed to identify a new Ahr agonist with inhibitory potentials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 49 publications
(62 reference statements)
4
30
0
Order By: Relevance
“…The aryl hydrocarbon receptor (AhR) is a member of the basic helix‐loop‐helix/Per‐ARNT‐SIM (bHLH/PAS) transcription factor family, and it has been previously suggested that it is a possible druggable target . It is ligand activated by a variety of synthetic and natural compounds .…”
Section: Aryl Hydrocarbon Receptormentioning
confidence: 99%
“…The aryl hydrocarbon receptor (AhR) is a member of the basic helix‐loop‐helix/Per‐ARNT‐SIM (bHLH/PAS) transcription factor family, and it has been previously suggested that it is a possible druggable target . It is ligand activated by a variety of synthetic and natural compounds .…”
Section: Aryl Hydrocarbon Receptormentioning
confidence: 99%
“…To date, although the role of AhR in cancer remains unclear, and some results are contradictory, many studies have shown the anticancer effects of AhR ligands in breast cancer. Flavipin, an AhR agonist, suppresses the migration and invasion of BC cells [34]. Genistein can confer sensitivity to triple-negative breast cancer for antiestrogen therapy by preventing and reversing AhR-dependent BRCA1 hypermethylation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we studied glyceollin effects in cell migration only in the MDA-MB-231 triple-negative breast cancer cells, because cells of this lineage represent the most metastatic type of breast cancer [45]. Moreover, previous studies showed that AhR is an important target of cell migration in triple-negative BC [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aryl hydrocarbon receptor (AhR) is a member of the basic helix-loop-helix/ Per-ARNT-SIM (bHLH/PAS) transcription factor family [1][2][3][4]. In its inactive state, the AhR resides in the cytosol of the cell as a complex with a number of other proteins.…”
Section: Introductionmentioning
confidence: 99%